Analysis of Factors Affecting Palm Oil (Elaesis Guineensis Jacq) Production in Central Kalimantan Region - Ramadan*, Vikram Edo; Hasmarini, Maulidyah Indira (Riwayat: Educational Journal of History and Humanities, 2023)
Oil palm is an industrial plantation crop that produces palm oil which can add value to the production of oil palm companies. The palm oil commodity is a commodity that can add to the country's foreign exchange because the value of palm oil has a high value. Palm oil production in Indonesia continues to grow every year. This study aims to find out about what factors affect the palm oil production variable in the Central Kalimantan region. This study uses panel data regression tools with data obtained from the Central Statistics Agency (BPS) and the Central Kalimantan Plantation Office. The results of the analysis of this study explain the factors of land area and labor have a positive and significant effect on oil palm production.